2022
DOI: 10.1111/ics.12759
|View full text |Cite
|
Sign up to set email alerts
|

Superior even skin tone and anti‐ageing benefit of a combination of 4‐hexylresorcinol and niacinamide

Abstract: Objectives To demonstrate the synergistic effect of 4‐hexylresorcinol (4‐HR) with niacinamide in boosting anti‐melanogenic efficacy in vitro and establish the in vivo efficacy and safety of the combination in a human trial. Methods Primary human epidermal melanocytes and 3D pigmented skin equivalents were treated with 4‐HR, niacinamide, and their combinations for their effect on pigmentation. This was followed by a randomized, double‐blind, split‐face clinical study in Chinese subjects, and effects on skin ton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Niacinamide is thought to inhibit melanosome transfer from melanocytes to keratinocytes and may also decrease collagen oxidation products improving skin sallowness. 5 A third mechanism of action to lighten facial pigment is inhibition of melanogenesis by enhancing the degradation of microphthalmiaassociated transcription factor (MITF) through activation of the extracellular signal-related protein kinase (ERK), which suppresses the expression of tryosinase (TYR) and tyrosinase-related proteins (TRP1 and TRP-2) genes. Glycerrhiza glabra (licorice) root acts in this manner with the bioactive ingredients being flavonoids and triterpene saponins.…”
Section: Discussionmentioning
confidence: 99%
“…Niacinamide is thought to inhibit melanosome transfer from melanocytes to keratinocytes and may also decrease collagen oxidation products improving skin sallowness. 5 A third mechanism of action to lighten facial pigment is inhibition of melanogenesis by enhancing the degradation of microphthalmiaassociated transcription factor (MITF) through activation of the extracellular signal-related protein kinase (ERK), which suppresses the expression of tryosinase (TYR) and tyrosinase-related proteins (TRP1 and TRP-2) genes. Glycerrhiza glabra (licorice) root acts in this manner with the bioactive ingredients being flavonoids and triterpene saponins.…”
Section: Discussionmentioning
confidence: 99%
“…As a substrate, instead of forming melanin, it gets metabolized to quinones and free radicals which cause lipid peroxidation, damaging the melanocyte membrane and leading to melanocyte cytotoxicity and depigmentation [126,127]. However, in a recent study designed to compare the effects of arbutin, HQ , and kojic acid with numerous resorcinol vis-à-vis inhibition of recombinant human tyrosinase [128,129], HQ was found to be ineffective against tyrosinase enzyme as compared to resorcinol (Figure 3). Thus, although considered to be a tyrosinase inhibitor for a long, it appears that the cytotoxic potential of HQ may largely contribute to its depigmentation effect.…”
Section: Cosmetic Agents For Hyperpigmentationmentioning
confidence: 99%
“…It is only in recent times that more potent tyrosinase inhibitors have been identified using enzymes sourced from human melanocytes or recombinant human tyrosinase protein with superior efficacy on melanotic conditions like solar lentigines and melasma, [129,168]. The commonly used compounds in the class of tyrosinase inhibitors include hydroquinone, arbutin, kojic acid, thiols, and resorcinol and among them, resorcinol derivatives are the most potent in enzyme inhibition [128,129]. It has been shown that resorcinol is a mono-oxygenase substrate and gets oxidized to hydroxy intermediate; 3-hydroxy-ortho-quinone, which results in irreversible elimination of Cu (0) of tyrosinase enzyme leading to inactivation of the enzyme [169,170].…”
Section: Sds-induced Human Occluded Patch Test (A) Irritation Score I...mentioning
confidence: 99%
See 2 more Smart Citations